CURRENT CHARACTERISTICS IN THE WATERS OF KHANH HOA PROVINCE DURING SOUTHWEST MONSOON PERIOD - Hoan, Pham Sy; Vinh, Nguyen Kim (Vietnam Journal of Marine Science and Technology, 2012)
This paper describes the characteristics of spatial and temporal variation of the currents in the Khanh Hoa province waters through observation during southwest monsoon period (July - August 2010). The main current direction is northeastern. The current speed decreases with depth and from south to north. The maximum current speed is 106cm/s. The tidal current is a main component of the general current. The residual current is weak with speed of about 3.9cm/s and  northwestern direction. The distribution features of current in the study area indicate the structure of circulation system in the strong upwelling area of South Vietnam waters. Besides, there is an eastward current system on the shelf of Nha Trang bay exists in the study area with speeds of about 10 to 26cm/s.